E-Learning Satisfaction and Learning Performance During COVID-19 Pandemic from Students’ Perspective - Siti Norziah Ismail; Mohamad Syafiq Abd Rahman (Research in Management of Technology and Business, 2022)
E-Learning implementation during the closure of higher education institutions due to COVID-19 pandemic without measurement and evaluation of its effect on the students engaged is one of the problems arise nowadays. E-Learning system which forced students to adapt the changes will indirectly lead to the dissatisfaction of students and their learning performance. Thus, this research aimed to identify the level of student’s E-Learning satisfaction during the closure of the higher education institution due to COVID-19 pandemic, to determine the relationship of E-Learning dimensions toward E-Learning satisfaction and lastly, to determine the relationship of E-Learning satisfaction towards student’s learning performance. The quantitative research approach was used to obtain data from respondents via an online survey questionnaire. There were a total of 285 students at the Academy of Language Studies, UiTM Shah Alam as the respondent. In order to fulfil the aims, the analysis of descriptive statistics and the Spearman correlation have been utilized to analyze the information. The primary results of this study showed that student’s E-Learning satisfaction were in a moderate and low level and there is a significant, positive and strong relationship between E-Learning dimensions toward E-Learning satisfaction and also E-Learning satisfaction toward learning performance. Findings of this research are able to help and provide the higher education institutions in Malaysia to be more understanding on student’s E-Learning satisfaction and learning performance during COVID-19 pandemic which allow the technology improvement, updating of the system and provide flexibility in implementation of E-Learning system.